The experience of black fathers concerning support for their wives/partners during labour - M.L. Sengane (AOSIS, 2009)
The goal of this article was to describe the experience of black fathers concerning support for their wives/partners during labour. The research design entailed an exploratory, descriptive, qualitative study that was contextual to clinical nursing. A phenomenological approach to nursing research was utilized, whereby unstructured interviews were conducted with ten black fathers. Two groups of black fathers were purposively selected for the study. Group 1 consisted of fathers who provided support to their wives/partners during labour and Group 2 consisted of fathers who did not provide support during labour. A literature control was undertaken to verify and recontextualize data. The results indicate that most of the fathers in Group 1 experienced negative feelings of nervousness, helplessness and anxiety due to lack of information concerning childbirth. These were coupled with positive feelings such as excitement, overwhelming delight and a sense of miracle. Most of the fathers in Group 2 expressed a feeling of wanting to be there. Lack of information, fear and cultural factors were identified as stumbling blocks. Conclusions drawn from the study included positive attitudes that needed to be enhanced as well as negative attitudes that needed counteracting. The guidelines were based on overcoming the following: cultural taboos; lack of knowledge and fears concerning childbirth; lack of interest in childbirth; and childbirth being regarded as a woman's department.